VALVE FUZZY RELIABILITY EVALUATION METHOD BASED ON THE INFLUENCE OF NON-CRITICAL STATE OF THE SYSTEM - YU ShuRong; LUO WeiYe; XUE RuiYuan; YIN SiMin; LI YongLin (Jixie qiangdu, 2020)
At present,the reliability of a single indicator is evaluated by a conventional reliability model.The results have only two states:the system is completely normal and the system is completely faulty.It is difficult to determine what state the valve system is between "good" and "failed".At the same time,ignoring the impact of non-critical state of the system on system reliability and evaluating method with a single indicator will result in insufficient evaluation results.Therefore,a fuzzy evaluation method based on triple index was proposed.The valve system failure probability PF,the failure probability considering the influence of non-critical states of the system PEF and the mean time between failures MTBF as the indicators to evaluate the reliability gray number clustering were considered.The failure probability considering the influence of the non-critical state of the system was obtained by the cumulative failure probability of the system and the number of expected state transitions.The experimental results indicated that the method can well describe the influence of the non-critical state of the system on the reliability and can determine the reliable level of the system.